Clinical and laboratory assessment of mineral deficiencies in grazing sheep and goats at Sana’a Governorate, Yemen - Ali Alshami, Abdulraqeb; Sharaf Al-Azazi, Aziz; Al-shawkany, Abdu-Alraoof; A. M. A. ALomaisi, Saleh; Ali Alrefaiey, Hamid; Saleh Al-Mawti, Bashar (Yemeni Journal of Agriculture & Veterinary Sciences, 2025)
Mineral deficiency represents a major health challenge affecting the productivity of small ruminants. This study aimed to evaluate mineral deficiencies in grazing sheep and goats at Sana’a Governorate, Yemen, and their association with hematological and biochemical parameters. A total of 200 local sheep (n=100) and goats (n=100), aged 1–4 years and maintained exclusively on pasture grazing were selected and investigated. Among these, 160 animals (80 sheep and 80 goats) showed signs of mineral deficiencies and considered as affected animals or deficient animals; while, 40 animals (20 sheep and 20 goats) appeared healthy and considered as controls. The clinical examination revealed, In deficient animals, the following clinical signs: easily detached and discolored hair or wool, alopecia, pale mucous membranes, inappetence, emaciation, and lethargy, with significantly elevated (P